Rapid expansion of preexisting nonleukemic hematopoietic clones frequently follows induction therapy for de novo AML - Wong, Terrence N; Miller, Christopher A; Klco, Jeffery M; Petti, Allegra; Demeter, Ryan; Helton, Nichole M; Li, Tiandao; Fulton, Robert S; Heath, Sharon E; Mardis, Elaine R; Westervelt, Peter; DiPersio, John F; et al. (Blood, 2016)
There is interest in using leukemia-gene panels and next-generation sequencing to assess acute myelogenous leukemia (AML) response to induction chemotherapy. Studies have shown that patients with AML in morphologic remission may continue to have clonal hematopoiesis with populations closely related to the founding AML clone and that this confers an increased risk of relapse. However, it remains unknown how induction chemotherapy influences the clonal evolution of a patient's nonleukemic hematopoietic population. Here, we report that 5 of 15 patients with genetic clearance of their founding AML clone after induction chemotherapy had a concomitant expansion of a hematopoietic population unrelated to the initial AML. These populations frequently harbored somatic mutations in genes recurrently mutated in AML or myelodysplastic syndromes and were detectable at very low frequencies at the time of AML diagnosis. These results suggest that nonleukemic hematopoietic stem and progenitor cells, harboring specific aging-acquired mutations, may have a competitive fitness advantage after induction chemotherapy, expand, and persist long after the completion of chemotherapy. Although the clinical importance of these "rising" clones remains to be determined, it will be important to distinguish them from leukemia-related populations when assessing for molecular responses to induction chemotherapy.